Development of high frequency dual output desktop PC power supply - Ng, Jhohan (2014)
In today’s world where efficiency and portability have become more important than ever, Switched Mode Power Supply (SMPS) is becoming the preferred design for power supply circuits. A SMPS is an electronic power supply that incorporates a switching regulator to generate the desired voltage which is essentially the power required for a device to work. As compare to Linear Power Supply (LPS), it has higher efficiency and significant reduction in size, weight and cost. However, designing of SMPS is more complicated than LPS.